Dinâmica de íons em células eletrolíticas - Freire, Fernando Carlos Messias (2008)
We analyze the dynamical response of the influence of the ions present in a liquid crystal submitted to a steplike external voltage. The time evolution of the system is investigated by solving the continuity equation, for the bulk and surface densities, taking into account the current of drift and diffusion. As well as, the influence of the adsorption at the interfaces on the transient phenomena occurring is investigated. In the limit of small amplitude of the applied potential, where the equation of problem can be linearized, we obtain an analytical solution for the bulk and surface densities of the ions. We also obtain, in this limit, the relaxation time for the transient phenomena. In addition, we analyze too if the concept of electrical impedance can be useful for to analyze a electrolytic cell submitted to a external voltage. For this last, we assume a simple harmonic function of the time. In all situations, the analysis is formed by solving numerically the differential equations governing the phenomenon of the redistribution of the ions and comparing the results with the ones obtained analytically.